Analisis Penerapan Sistem Transaksi Non Tunai Dalam Pengelolaan Keuangan Daerah Pada Badan Keuangan Dan Aset Daerah Kabupaten Dairi - Fitri Rosalina N. Samosir; Badaruddin Badaruddin; Nina Siti Salmaniah Siregar (PERSPEKTIF, 2022)
This study aims to determine, analyze and factor constraints in the application of non-cash transaction systems in regional financial management at the Regional Finance and Assets Agency of Dairi Regency. This study uses a descriptive method with a qualitative approach, namely taking data related to the problems to be studied so that it can be described descriptively, qualitatively and comprehensively, which describes the prevailing reality and discusses the problems raised related to the Application of the Non-Cash Transaction System. In Regional Financial Management at the Regional Finance and Assets Agency of Dairi Regency. The results showed that the Regional Finance and Assets Agency of Dairi Regency has not been able to fully implement non-cash financial transactions on revenue receipts and expenditures as stipulated in Perbup Dairi No. 43 of 2020. The obstacles faced in implementing or implementing transactions have not been overcome, because there are indeed many field conditions that are not in accordance with the implementation of non-cash transactions. Employees are still not able to handle non-cash transaction processing, while the training program is inadequate because the available equipment, especially for practicing, is very limited.